Exploring the puzzle of human reproduction: Register data based evidence from France and Germany - Cäcilia Lipowski; Ralf A. Wilke; Bertrand M. Koebel (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
Birth rates differ strongly across European states, despite the deep economic harmonisation process related to European integration. This study uses large scale administrative data from France and Germany to analyse and directly compare fertility patterns in two major European economies over a period of 15 years. Strong evidence is found that opportunity costs play a role in fertility decisions, and for a positive income effect for females with high earnings. Females in Germany adapt their fertility behaviour more strongly in response to economic incentives than their counterpartsin France. This is explained by pronounced differences in the national approaches to childcare support.
Keywords: J13; J11; C23; C25; 330; family policy; fertility behaviour; count data; panel data